A Blockchain-Based Protocol for Fair Delivery for Receipts - M. Francisca Hinarejos; Josep-Lluis Ferrer-Gomila; Andreu-Pere Isern-Deyà; Gerardo-Francisco Chévez-Alvarado (Future Internet)
Message exchange for acknowledgment of receipt (e.g., for services that provide recipients with certain documents, such as sanctions, summonses, or requirements, which are often sent by public administrations) has traditionally been provided through protocols based on the use of trusted third parties (TTPs). More recently, solutions have been proposed that totally or partially replace the TTP with a blockchain. However, an analysis of these proposals reveals that they have one or more of the following drawbacks: failure to meet confidentiality requirements, the use of TTPs, and susceptibility to attacks that make them unfair. In this paper, we present a method of providing fair delivery for receipts based on a blockchain that does not suffer from the above disadvantages: it is fair and confidential and does not use a TTP. In addition, we demonstrate the feasibility of the protocol through a cost analysis and a proof-of-concept implementation, showing that our solution is more economical than existing solutions, and can be considered cost-effective even under low time requirements.